Energy Efficiency Optimization in Mechanical Systems: Innovative Approaches in Industrial Applications - Susan Margaret Clark; Patricia Rose Wilson; Charles Patrick Scott (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Energy efficiency has become a cornerstone in industrial optimization, reducing operational costs and contributing to sustainability. This paper reviews key innovative approaches in mechanical systems used to enhance energy efficiency within industrial applications. It covers advances in system design, smart technologies, automation, and predictive maintenance. By understanding these techniques, industries can make strides toward greener production processes, lower energy costs, and reduced environmental impact.